2011
DOI: 10.1002/cne.22722
|View full text |Cite
|
Sign up to set email alerts
|

Migration of neuronal precursors from the telencephalic ventricular zone into the olfactory bulb in adult zebrafish

Abstract: In the brain of adult mammals, neuronal precursors are generated in the subventricular zone in the lateral wall of the lateral ventricles and migrate into the olfactory bulbs (OBs) through a well-studied route called the rostral migratory stream (RMS). Recent studies have revealed that a comparable neural stem cell niche is widely conserved at the ventricular wall of adult vertebrates. However, little is known about the migration route of neuronal precursors in nonmammalian adult brains. Here, we show that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 84 publications
12
87
0
Order By: Relevance
“…This behavior is in accordance with the findings of Zupanc et al [50,51] that observed, in the adult fish, RDGc actively divided to produce new neurons in the injured brain and guided them to the lesion site to regenerate the neural tissue [50,51]. Such evidences were supportive for the role exerted by RDGc in adult teleost brain to be responsible for the strong ability of neural tissue regeneration [52]. The possibility that RDGc might exist as radially oriented cells is absolutely dissimilar in mammals, where RDGc were transformed into multipolar astrocytes in the adult brain, no longer regenerating [52,53].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This behavior is in accordance with the findings of Zupanc et al [50,51] that observed, in the adult fish, RDGc actively divided to produce new neurons in the injured brain and guided them to the lesion site to regenerate the neural tissue [50,51]. Such evidences were supportive for the role exerted by RDGc in adult teleost brain to be responsible for the strong ability of neural tissue regeneration [52]. The possibility that RDGc might exist as radially oriented cells is absolutely dissimilar in mammals, where RDGc were transformed into multipolar astrocytes in the adult brain, no longer regenerating [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…Such evidences were supportive for the role exerted by RDGc in adult teleost brain to be responsible for the strong ability of neural tissue regeneration [52]. The possibility that RDGc might exist as radially oriented cells is absolutely dissimilar in mammals, where RDGc were transformed into multipolar astrocytes in the adult brain, no longer regenerating [52,53].…”
Section: Discussionmentioning
confidence: 68%
“…A comparable neural stem cell niche in the adult brain is widely conserved at the ventricular wall 1,[111][112][113][114][115] (Fig. 6), where embryonic neural stem cells are located in the developing brain.…”
Section: Adult Neurogenesis In Various Speciesmentioning
confidence: 99%
“…6). 112 Moreover, a continuous migratory stream of PSA-NCAM+ neuronal progenitors extends from the VZ to the OB, but the neurons do not move through glial tunnels. Time-lapse imaging using Tg(ngn1:gfp) fish demonstrated that neuronal progenitors migrate rostrally along blood vessels in the RMS toward the OB, indicating that the PSA-NCAM+ stream is the functional route for the migration of neuronal progenitors in the adult zebrafish brain.…”
Section: Adult Neurogenesis In Various Speciesmentioning
confidence: 99%
“…A recent study indicates that neuronal precursors might also use blood vessels as a physical substrate for their migration (Saghatelyan 2009). The vasculature-guided (vasophilic) migration of neuronal precursors has been observed not only under normal conditions, such as in the olfactory bulb (OB) (Bovetti et al 2007;Kishimoto et al 2011;Bozoyan et al 2012), but also in brains undergoing pathological conditions, such as strokes (Saghatelyan 2009). The mechanism of the correlation between nerves and vasculature is not yet clear.…”
Section: Introductionmentioning
confidence: 99%